2021
DOI: 10.1039/d0sc05329e
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on the molecular simulation of DNA from structural and functional aspects

Abstract: An overview of atomistic simulations on the effect of sequences, base modifications, environmental factors and protein binding on DNA’s hierarchical structure and dynamics in the context of protein–DNA interactions, gene regulation and structural organization of chromatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 123 publications
(289 reference statements)
0
6
0
Order By: Relevance
“…Thus, the protonation state of cytosine bases helps to stabilize the stacked base pairs within the i-motif core at low pHs. It was found that an imino proton on the N3 atom of cytosine contributes to the formation of planar hydrogen-bonded hemiprotonated C:C + pairs, leading to base pairing that is stronger than classical Watson–Crick base pairing. , In the absence of a proton, cytosine bases can also form a pair through C:C W:W trans base pairing, where one cytosine base is shared along the base pair plane and forms two hydrogen bonds between the N4 atom of one cytosine and the N3 atom of another . We studied the conformational preference and base pairing of closely interacting cytosine bases in the i-motif core at different pHs.…”
mentioning
confidence: 99%
“…Thus, the protonation state of cytosine bases helps to stabilize the stacked base pairs within the i-motif core at low pHs. It was found that an imino proton on the N3 atom of cytosine contributes to the formation of planar hydrogen-bonded hemiprotonated C:C + pairs, leading to base pairing that is stronger than classical Watson–Crick base pairing. , In the absence of a proton, cytosine bases can also form a pair through C:C W:W trans base pairing, where one cytosine base is shared along the base pair plane and forms two hydrogen bonds between the N4 atom of one cytosine and the N3 atom of another . We studied the conformational preference and base pairing of closely interacting cytosine bases in the i-motif core at different pHs.…”
mentioning
confidence: 99%
“…3,4 An MD simulation yields a molecular time trace that can complement experiments by either aiding in interpretation or providing predictions. MD simulations allow studying a wide range of molecular phenomena relevant to biomolecular systems, [5][6][7] and can increase the accessibility of processes that, to date, cannot be observed in experiments, such as the relaxation of DNA to a specific ionic environment. [8][9][10][11] Tailored strategies for modeling reaction mechanisms of ligands interacting with DNA can utilize MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“… 8 10 Therefore, accurate information about base flip dynamics is of high interest and importance. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…8−10 Therefore, accurate information about base flip dynamics is of high interest and importance. 10,11 Thymine glycol (5,6-dihydro-5,6-dihydroxy thymine; Tg) is the most common oxidation product of thymine. Approximately 400 Tg residues are formed in a normal cell each day, and 10−20% of genome damages have been attributed to the oxidative conversion of thymine to Tg.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation